2016
DOI: 10.1007/s10552-016-0801-y
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and mammographic density measurements in the Nurses’ Health Study II

Abstract: Purpose Endometriosis and mammographic density have been hypothesized to be influenced by sex-steroid hormonal exposures in adolescence and early adulthood. We investigated the association between endometriosis and mammographic density, a consistent and independent risk factor for breast cancer. Methods We conducted a cross-sectional analysis among 1,581 pre- and post-menopausal women not previously diagnosed with breast cancer in the Nurses’ Health Study II cohort. We measured average percent mammographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
1
1
Order By: Relevance
“…It also infers that sex hormones alone are not implicated in female cancers after endometriosis. To the best of our knowledge, the only study which evaluated the relationship between endometriosis and MBD was that of Farland et al [15]. According to this study, endometriosis was not found to be associated with mammographic density, which was in contrast with our nding.…”
Section: Discussioncontrasting
confidence: 90%
“…It also infers that sex hormones alone are not implicated in female cancers after endometriosis. To the best of our knowledge, the only study which evaluated the relationship between endometriosis and MBD was that of Farland et al [15]. According to this study, endometriosis was not found to be associated with mammographic density, which was in contrast with our nding.…”
Section: Discussioncontrasting
confidence: 90%
“…It also infers that sex hormones alone are not implicated in female cancers after endometriosis. To the best of our knowledge, the only study which evaluated the relationship between endometriosis and MBD was that of Farland et al [ 20 ]. According to this study, endometriosis was not found to be associated with mammographic density, which was in contrast with our finding.…”
Section: Discussionmentioning
confidence: 99%